2007
DOI: 10.1016/j.cmet.2007.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Aging-Associated Reductions in AMP-Activated Protein Kinase Activity and Mitochondrial Biogenesis

Abstract: SummaryRecent studies have demonstrated a strong relationship between aging-associated reductions in mitochondrial function, dysregulated intracellular lipid metabolism, and insulin resistance. Given the important role of the AMP-activated protein kinase (AMPK) in the regulation of fat oxidation and mitochondrial biogenesis, we examined AMPK activity in young and old rats and found that acute stimulation of AMPK-α2 activity by 5′-aminoimidazole-4-carboxamide-1-β-D-ribofuranoside (AICAR) and exercise was blunte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

30
356
6
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 479 publications
(395 citation statements)
references
References 19 publications
30
356
6
3
Order By: Relevance
“…It acts as a cancer chemoprevention agent [16], a powerful anti-inflammatory factor and an antioxidant agent [17,18]. Its cardiovascular properties, including inhibition of platelet aggregation and promotion of vasodilation by enhancing the production of NO [19] have also been described [15,20] and recent studies have reported its beneficial effects against ageing and metabolic diseases [21][22][23][24]. Resveratrol has been described as a potent activator of AMPK in several tissues and cell lines, i.e, HepG2 [24], C2C12 myotubes [25] neuronal cell lines and neurons [26].…”
Section: Introductionmentioning
confidence: 99%
“…It acts as a cancer chemoprevention agent [16], a powerful anti-inflammatory factor and an antioxidant agent [17,18]. Its cardiovascular properties, including inhibition of platelet aggregation and promotion of vasodilation by enhancing the production of NO [19] have also been described [15,20] and recent studies have reported its beneficial effects against ageing and metabolic diseases [21][22][23][24]. Resveratrol has been described as a potent activator of AMPK in several tissues and cell lines, i.e, HepG2 [24], C2C12 myotubes [25] neuronal cell lines and neurons [26].…”
Section: Introductionmentioning
confidence: 99%
“…In certain circumstances, such as aging, the mechanisms for why or how mitochondrial function and dynamics become abnormal are unknown (Petersen et al 2003;Reznick et al 2007). Regardless of the mechanism, however, data gleaned from signaling studies suggest that certain elements of these pathways can be leveraged to either prevent or attenuate a wide array of mitochondrial dysfunctions.…”
Section: Therapeutic Potential Of Signaling Pathways For the Attenuatmentioning
confidence: 99%
“…Guanidinopropionic acid feeding has been shown to increase mitochondrial biogenesis by elevated levels of PGC‐1α mRNA expression, mitochondrial density, δ‐ALAS mRNA expression, and cytochrome c protein expression (Reznick et al ., 2007). Our results demonstrate that β‐GPA decreases the level of LD and LDH, indicating the decreased glycolysis.…”
Section: Discussionmentioning
confidence: 99%
“…The finding that β‐GPA can activate AMPK in the brain is consistent with previous reports showing that β‐GPA increases the AMPK activity in peripheral tissues, such as skeletal muscle (Reznick et al ., 2007). We found that β‐GPA upregulated the AMPK activity in Drosophila , and this upregulation was ubiquitous, as the levels of phosphorylated AMPK were similarly upregulated in all main segments of Drosophila , such as heads, thoraces, and abdomens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation